Manic Episode after Ventricular-Peritoneal Shunt Replacement in a Patient with Radiation-Induced Hydrocephalus: The Role of Lifetime Subthreshold Bipolar Features. (12th January 2014) - Callari, Antonio; Mantua, Valentina; Miniati, Mario; Benvenuti, Antonella; Mauri, Mauro; Dell'Osso, Liliana
Abstract : We present a case report of a woman hospitalized for a ventricular-peritoneal shunting replacement, who developed a manic episode with psychotic symptoms after hydrocephalus resolution. We have no knowledge of cases of manic episodes due to hydrocephalus resolution by ventricular-peritoneal shunt replacement, although previous case reports have suggested that hydrocephalus might induce rapid-onset affective episodes or mood cycles. The patient's history revealed the lifetime presence of signs and features belonging to the subthreshold bipolar spectrum, in absence of previous full-blown episodes of a bipolar disorder. Our hypothesis is that such lifetime sub-threshold bipolar features represented precursors of the subsequent full-blown manic episode, triggered by an upregulated binding of striatum D2 receptors after the ventricular-peritoneal shunt replacement.